2003
DOI: 10.1097/01.blo.0000071755.41516.a0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Single Technique Ankle Arthrodesis in Patients With Rheumatoid Arthritis

Abstract: The established treatment for severe rheumatoid arthritis in the ankle is arthrodesis. Numerous reports in the literature describe outcomes in patients with degenerative and posttraumatic arthrosis and rheumatoid disease. This has led to results that are difficult to interpret. In addition, in the few studies that have evaluated patients with rheumatoid disease many techniques of arthrodesis are reported, further confounding assessment of one fusion method. One technique of 20 ankle fusions in patients with rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
0
19
1
1
Order By: Relevance
“…The two groups had similar demographics, time of onset of symptoms, and preoperative outcome scores. While not designed as specific scores for the hindfoot, the AOFAS hindfoot and the SF-36 scores have been used previously for this purpose [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two groups had similar demographics, time of onset of symptoms, and preoperative outcome scores. While not designed as specific scores for the hindfoot, the AOFAS hindfoot and the SF-36 scores have been used previously for this purpose [10].…”
Section: Discussionmentioning
confidence: 99%
“…The AOFAS ankle-hindfoot score evaluates pain (40 points), function (50 points), and alignment (10 points). The SF-36v2 is a general health survey with physical and mental components and has been validated internally and externally in foot and ankle hindfoot surgery [10,22].…”
Section: Methodsmentioning
confidence: 99%
“…Techniques of internal and external fixation have been reported with varying degrees of success [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . The outcomes of intramedullary rodding, a common alternative to pantalar arthrodesis with plating, have often been reported in the literature.…”
Section: Surgical Optionsmentioning
confidence: 99%
“…However this review revealed the methodological quality of included studies no certain cut-off value was applied as exclusion criterion regarding the small number of studies (17). Statistical parameters as the standard deviation, which was absent in 4 studies [ 19 , 21 , 23 , 24 , 26 ] prevented measuring the effect size.…”
Section: Discussionmentioning
confidence: 99%